Translating application from visual basic to Active Server Pages (ASP) using visual basic systems / Mohd Aziz Mohamad Napiah - Mohamad Napiah, Mohd Aziz (Faculty of Information Technology and Quantitative Sciences, 2005)
The Simple Translator from VB to ASP System represents a system that provides a systematic approach of the new learner to understanding the basic concept of Visual Basic and Active Server Pages (ASP). This system has been developed to give a solution the interface or scripting not supported with another alternative so that users can still use the control. Mostly, User do not know the best way to settle their problem when to practice the programming in variety languages. Therefore, they need a system that helps them to find out the solution with efficient and interactive. The objective of this study is to develop a system that using application as reference that can help user to understand either in Visual Basic or Active Server Pages (ASP). It also focuses on to develop an interface that attractive to user so that they like to use this system to learn the programming. The methodology of this study is based on System Development Life Cycle (SDLC). By doing the study on system analysis, it help researcher for fully understand and developing the system. It also involves designing the interface of the system according to interface and scripting. At the end of the study, the researcher hope the system can help user in learning and studying programming languages efficiently.